Early Visual Processing is Affected by Clinical Subtype in Patients with Unilateral Spatial Neglect: A Magnetoencephalography Study - Mizuno, Katsuhiro; Tsuji, Tetsuya; Rossetti, Yves; Pisella, Laure; Ohde, Hisao; Liu, Meigen (Frontiers in Human Neuroscience, 2013)
OBJECTIVE: To determine whether visual evoked fields (VEFs) elicited by right and left hemifield stimulation differ in patients with unilateral spatial neglect that results from cerebrovascular accident. METHODS: Pattern-reversal stimulation of the right and left hemifield was performed in three patients with left unilateral spatial neglect. Magnetoencephalography was recorded using a 160-channel system, and VEFs were quantified in the 400 ms after each stimulus. The presence or absence of VEF components at around 100 ms (P100m component) and 145 ms (N145m component) after stimulus onset was determined. The source of the VEF was determined using a single equivalent current dipole model for spherical volume conduction. All patients were evaluated using the behavioral inattention test (BIT). RESULTS: In response to right hemifield stimulation, the P100m and N145m components of the VEF were evident in all three patients. In response to left hemifield stimulation, both components were evident in Patient 3, whereas only the P100m component was evident in Patient 1 and only the N145m component was evident in Patient 2. Patient 1 exhibited impairments on the line bisection and cancellation tasks of the BIT, Patient 2 exhibited impairments on the copying, drawing and cancellation tasks of the BIT, and Patient 3 exhibited impairments on the cancellation task of the BIT. CONCLUSIONS: These results demonstrate that early VEFs are disrupted in patients with unilateral spatial neglect and support the concept that deficits in visual processing differ according to the clinical subtype of unilateral spatial neglect and the lesion location. This study also demonstrates the feasibility of using magnetoencephalography to explore subtypes of neglect.